Legitimacy of the Notary Inspection Board within the Indonesian Legal Framework: Legitimitasi Majelis Pemeriksa Notaris dalam Kerangka Hukum Indonesia - Mubaroq, Ahmad Muhajir Firrizqi; Muljosantoso, Sugeng; Anggraeni, Dessi; Tabroni (Rechtsidee, 2023)
This study examines the position and legitimacy of the establishment of a Notary Inspection Board within the Indonesian legal framework, with a particular focus on the Law on Notary Position (UUJN) and Ministerial Regulation of Law and Human Rights (Permenkumham) Number 15 of 2020. The research employs a normative legal method to scrutinize norms within the UUJN and Permenkumham 15/2020, prompted by perceived normative disharmony between these regulations regarding oversight and sanctioning of notaries. Contrary to prior research that suggested a normative disharmony, this study finds that the Inspection Board acts on behalf of the Notary Oversight Board, as its members are part of the latter, with duties delegated by the Chairperson of the Notary Oversight Board. Thus, Permenkumham 15/2020 does not contradict the UUJN. Nevertheless, for greater clarity, the study recommends revisions to Permenkumham 15/2020, emphasizing the basis of authority and formation of the Inspection Board.Highlights: No legal disharmony between Ministerial Regulation 15/2020 and the Law on Notary Position. Notary Examination Board is part of the Notary Supervisory Board. Amendments to Regulation 15/2020 are suggested for clearer authority and establishment process. Keywords: Notary Examination Board, Notary Supervisory Board, Ministerial Regulation 15/2020, Law on Notary Position, legal harmonization.